Epidemiology of psoriatic arthritis - C. Salvarani; N. Pipitone; M. Catanoso (PAGEPress Publications, 2012)
Epidemiological studies on psoriatic arthritis have long been hampered by the absence of widely accepted classification criteria. The development of the CASPAR (ClASsification criteria for Psoriatic ARthritis) criteria has recently provided the framework for conducting epidemiological studies in psoriatic arthritis using uniform recruitment criteria. However, so far, only a minority of studies have adopted such criteria. In addition to the lack of shared classification criteria, differences in study settings, designs, and ascertainment methods have contributed to yield substantial disparities in the estimates of the incidence (from 3,02 to 23,1 cases per 100,000 people) and prevalence (from 49,1 to 420 cases per 100,000 people) of psoriatic arthritis around the globe. Overall, the available data suggests that the prevalence of psoriasis in the general population is approximately 2-3%, with about a third of patients with psoriasis having arthritis. Therefore, psoriatic arthritis may affect 0,3- 1,0% of the population, a frequency not dissimilar from that of rheumatoid arthritis. Future epidemiological studies should be carried out in larger numbers of patients diagnosed using consistent criteria.